Design and Optimization of Detection Antenna for Corona Discharge in High-voltage Transmission Lines. Issue 6 (April 2020) - Xiao, Xiaoming; Hu, Weinan; Ran, Jun; Xu, Zheng; Hei, Guoyu; Han, Xintong; Zhao, Lipeng
Abstract: Corona discharge on high-voltage transmission lines is a common phenomenon in power systems. It results from poor contact between insulators and lines, and broken strands on transmission lines. Long-term corona discharges may lead to more serious power grids accidents. Hence, it is of great importance to effectively detect the occurrence of corona discharge. The Hilbert Fractal Antenna is a wide-band, small-sized antenna which can be carried by the unmanned aerial vehicle for close-range detection and accurately position fault points of corona discharge. In this paper, the finite element method is used to study the 5th order Hilbert fractal antenna. The research focuses on the different feeding positions of the antenna. By studying the different feeding positions of the antenna, we determine a miniaturized antenna which can be used for corona discharge detection of high-voltage transmission lines.